Occurrence of Elevated Nitrogenous and Phosphorus in Groundwater Sources Used in Unplanned Settlements, Dar Es Salaam - Tanzania - Leonard, Leopord Sibomana; Mato, Rubhera R.A.M.; Kaseva, Mengiseny E. (International Journal of Environment, 2022)
Groundwater in unplanned settlements is stressed by multiple pollution sources threatening health of consumers. Elevated nitrogen and phosphorus affect the quality of groundwater as they leach through the soil to groundwater. This study aimed at establishing variations of nitrogenous and phosphorus compounds in 75 boreholes used in 8 unplanned settlements in Dar es Salaam, Tanzania. Laboratory analysis using Spectrophotometer DR/4000 was conducted at Ardhi University. Principal Component Analysis was conducted by using Paleontological Statistics (PAST) software, version 3.08 and statistical significance set at p < 0.05. Results indicated that about 84% and 73.3% of sampled boreholes during wet and dry seasons, respectively had nitrate nitrogen greater than WHO recommendations for drinking water quality standards. Concentration of NO2-N showed that 12% and 14.7% of sampled boreholes during wet and dry seasons, respectively were greater than 0.9 mg/L TZS (574:2016) recommended guidelines. Phosphate concentration was greater than 2.2 mg/L TZS (574:2016) recommended guidelines in 49.3% and 12% of sampled boreholes during both wet and dry seasons, respectively. These results indicated that consuming such polluted water may be unsafe to infants and older people and therefore alternative drinking water source is recommended.